The impact of performance appraisal on employee job performance in public sector Universities of Khyber Pakhtunkhwa, Pakistan - Khan, Muhammad Asad; Ismail, Fadillah; Yusoff, Rosman Md; Hussain, Altaf; Mohd Yunus, Fazlulaini (Science Publishing Corporation (SPC), 2018)
The purpose of this research is to investigate the relationship of performance appraisal and fairness of performance appraisal with employee job performance to get empirical findings of such relationship in higher education institutions of Pakistan. This study is comprised of a survey based questionnaire. The data was collected from 150 respondents of public sector universities of Khyber Pakhtunkhwa via self-administered questionnaire. A sum of 300 questionnaires was distributed among the faculty members of the public sector universities of Khyber Pakhtunkhwa, Pakistan out of which 150 were returned back so the response rate is 50%. Results of this study showed that there was significant and positive relationship between performance appraisal, fairness and employee job performance in public sector universities of Khyber Pakhtunkhwa, Pakistan. In other words, it means that if performance appraisal of the universities is fair enough, accurate then employee will be satisfied and get motivated to enhance their performance in particular and organizational performance in general. Such research has utilized large sample size and has not been done before, to the best of researcher’s knowledge. This study has significance for the policy makers of higher education and universities and researchers can also get benefit of it in future.